Twelve-tone tonality - Perle, George (Berkeley University of California Press, 1996)
In this classic work, George Perle argues that the seemingly disparate styles of post-triadic music in fact share common structural elements. These elements collectively imply a new tonality as "natural" and coherent as the major-minor tonality that was the basis of a common musical language in the past. His book describes the foundational assumptions of this post-diatonic tonality and illustrates its compositional functions with numerous musical examples.The second edition of Twelve-Tone Tonality is enlarged by eleven new chapters, some of which are "postscripts" to earlier chapters--clarifying, elucidating, and expanding upon concepts discussed in the original edition. Others discuss new developments in the theory and practice of twelve-tone tonality, including voice-leading implications of the system and dissonance treatment.